OP0015 Induction of remission and maintenance in early, aggressive rheumatoid arthritis using adalimumab in combination with methotrexate with or without short-term high-dose glucocorticoids: results of a phase iv multicenter, randomized, double blind study (clintrial.gov: NCT00480272). (15th June 2017) - Caporali, R; Montecucco, C; Bocci, E Bartoloni; Vitolo, B; Prisco, E; Klersy, C; Giacomelli, R; Triolo, G; Cutolo, M; Marchesoni, A; Gremese, E; Iannuccelli, C; et al.
Abstract : Background: Remission is the current aim of early RA treatment. In patients with early, aggressive RA, combination with adalimumab (ADA) plus methotrexate (MTX) was superior to either MTX or ADA alone in obtaining clinical remission. Moreover, it has been demonstrated that a short-term aggressive treatment with high-dose glucocorticoids (GC) plus conventional DMARDs lead to long-term (up to 5 years) benefits. Objectives: To compare the proportion of patients who achieve remission at 12 months, between two groups of subjects treated with ADA + MTX + high dose GC (intensive) and ADA + MTX + placebo (standard), and to evaluate the proportion of those maintaining remission at 24 months, after discontinuation of GC at 6 and ADA at 12 months. Methods: The main inclusion criteria were: active RA, disease duration ≤1 year, GC and MTX-naïvity, at least one predictor of aggressive disease. All subjects received ADA for 12 months and MTX (20 mg/w) to the end of month 24. Subjects were randomized to receive prednisone (orally, 50 mg/d, progressively tapered to 6.25 mg and stopped at month 6) or placebo. Response was evaluated using DAS28, CDAI, SDAI and ACR response criteria. The difference in rate and 95% CI will be computed with a binomial regression model and identity link, while clustering on center. An intention-to-treat analysis was performed. Results: 118 patients were assigned to standard and 115 patients to intensive group. Remission (DAS28<2.6, SDAI≤3.3, CDAI≤2.8) at 1 year in standard vs intensive group were: 56.25% vs 45.28% (RD= -11%, 95% CI -23 to1, p=0.07), 30.36% vs 21.69% (RD= -9%, 95% CI -20 to 3, p=0.14), and 28.57% vs 22.64% (RD= -6%, 95% CI -18 to 6, p=0.34). DAS28 remission at 2 years was 36.84% in standard vs 30.93% in intensive (RD= -6%, 95% CI -17 to 5, p=0.28). No superiority of the intensive group was seen in ACR20–50–70 response rates at 4, 8, 12, 24 months. The overall frequency of adverse events (AE) in patients that completed the trial was comparable between groups. The percentage of patients who discontinued for AE was higher in the intensive group (9.32% in standard vs 16.52% in intensive, RD=7%, 95% CI 1 to 13, p=0.01). Conclusions: Our results confirm that intensive treatment with biologics in early, aggressive RA might be considered to induce and maintain clinical remission. The addition of high-dose GC to a first line treatment with ADA and MTX did not prove to induce a further improvement in efficacy. Although these results should be tested with other biologic therapies, the high rate of drop out for AE in the intensive group should be carefully considered in the risk-benefit ratio. Disclosure of Interest: None declared